Muzyka u Matejków - Kłak-Ambrożkiewicz, Marta (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2023)
Jan Matejko is the author of more than three hundred twenty oil paintings, several thousand drawing sketches, a couple of hundred projects of the polychrome, stained glass, altars and statues. The artistic activity of Jan Matejko (1838–1893) was focused on the historical – patriotic interests as well as the research passion of mastering the relicts of the past and their protection against damage. The artist died in 1893. After his death the idea of founding a biographical museum in his house arose. The institution, apart from conducting research on the life and work of the artist, deals with various forms of popularization of this knowledge. “Music making at the Matejko” family referring to the domestic and family music making, has become the other form.